STUDY ON THE DENTAL STUDENTS ATTITUDE TOWARD PATIENTS WITH CHRONIC DISEASES - Diana Diaconu-Popa; Monica Silvia Tatarciuc; Cristina Gena Dascălu; Anca Mihaela Viţalariu (Romanian Society of Oral Rehabilitation, 2016)
In dental medicine, like in every medical field, the professional activity is coordinated by the principles of Code of Medical Deontology that contains rules of moral behavior and professional duties. The ethical dentist strives to do that what is right and good, and the ethical principles are an instrument to support it in this quest. The dental students should possess not only knowledge, skills and technical competences but also those traits of character that foster adherence to ethical principles- qualities of compassion, kindness, integrity, fairness and charity complement the ethical practice of dentistry and help to define the true professional. For this study we developed a ten items questionnaire in order to appreciate the attitude of the future dentists toward dental treatment in patients with chronic transmissible diseases. The thirdsixth year students answered affirmatively or negatively, including a short motivation for every answer. Results were statistical and comparatively analyzed according to the year of study of the respondent. The present research was intended as a starting point for a broader analysis of the dentist's attitude toward dental treatment of the patients with chronic transmissible diseases in Romania. The conclusions of our study demonstrate that the students of the Faculty of Dental Medicine guide their practice work based on a series of basic ethical principles. They concluded that the notions of bioethics bring more information which will provide scientific and objective support to this attitude and will create prerequisites for a legitimate therapeutic decision